Emergent Trends in Nigeria’s Popular Entertainment: Cross-Dressing and Blurred Identity in Social Media Skits - Elizabeth Onyewuchi Ben-Iheanacho; Emefiele Felix Gbenoba; Shaibu Husseini (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This paper explores the relationship between mass media and its audience, specifically in Nigeria where this field is under-studied. Since its debut in 1959 as a medium of domestic entertainment, television in Nigeria has been a wonderland for new vistas and foreign and strange concepts that became trendsetters for viewers’ astonishment and enthusiastic lifestyle emulation. This study uses qualitative methods, including Key Informant Interviews and secondary analysis, to explore cross-dressing as a cultural phenomenon. The theoretical framework is based on the gratification and technological determinism theories. The study examines how technological advancements have enabled the normalization of